Care and attention - Sevenhuijsen, S.L. (South African Journal of Higher Education, 2018)
Attention is an important aspect of care in both public and private realms. Attention is a normative concept, which is embedded in caring practices. Attentiveness or attention the first element of interconnected phases of care and pertains to ‘caring about’, or perceiving the need for care, which initiates the caring process. This paper introduces the notion of “active attention” as an ideal image of attention enabling the practice of good care.